2018
DOI: 10.1038/s41416-018-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I study of the novel immunomodulatory agent PG545 (pixatimod) in subjects with advanced solid tumours

Abstract: PG545 demonstrated a tolerable safety profile, proportional PK, evidence of immune cell stimulation and disease control in some subjects. Taken together, these data support the proposed mechanism of action, which represents a promising approach for use in combination with existing therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 38 publications
(45 reference statements)
5
78
0
Order By: Relevance
“…PG545 has been selected over the PG500 series of heparan sulfate mimetics for the ability to inhibit both angiogenesis and heparanase activity and was selected as the lead clinical candidate for oncology [191]. Eight years after, PG545 was then evaluated on a Phase I study in patients with advanced solid malignancies that had relapsed or was refractory to standard therapy, and showed a disease control up to 24 weeks in 38% of evaluable subjects with increases in innate immune cell activation, plasma IFNγ, TNFα, IP-10, and MCP-1 [192].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…PG545 has been selected over the PG500 series of heparan sulfate mimetics for the ability to inhibit both angiogenesis and heparanase activity and was selected as the lead clinical candidate for oncology [191]. Eight years after, PG545 was then evaluated on a Phase I study in patients with advanced solid malignancies that had relapsed or was refractory to standard therapy, and showed a disease control up to 24 weeks in 38% of evaluable subjects with increases in innate immune cell activation, plasma IFNγ, TNFα, IP-10, and MCP-1 [192].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Immunohistochemistry, in situ hybridization, quantitative polymerase chain reaction (qPCR) and immunoblot analyses demonstrate that heparanase expression is enhanced in all major types of cancers (i.e., carcinomas, sarcomas and hematological malignancies) . Numerous clinical association studies have consistently demonstrated that upregulated heparanase expression correlates with enhanced metastasis and poor prognosis, thus confirming the prometastatic function of heparanase and encouraging the development of heparanase inhibitors as antitumor therapeutics . More recent studies provided compelling evidence that tie heparanase with all steps of tumor formation including tumor initiation, growth, metastasis and chemoresistance .…”
Section: Introductionmentioning
confidence: 98%
“…Heparan sulfate mimetics have emerged as potential therapies against various types of cancer (1)(2)(3)(4). These agents are thought to work via inhibition of heparanase (5)(6)(7), an enzyme associated with tumor cell invasion and angiogenesis (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…PG545 is reported to function by blocking the catalytic center of heparinase and competing for the HSbinding domain (11,19). PG545 is currently under evaluation in human clinical trials for use in treating solid tumors after having demonstrated efficacy against tumor angiogenesis and metastasis in multiple animal studies (1,3,20,21). PG545 has also demonstrated efficacy against lymphoma and may also have utility in other, non-neoplastic inflammatory disorders, such as acute kidney injury, atherosclerosis, and viral infection (2,9,22,23).…”
Section: Introductionmentioning
confidence: 99%